“I Must Keep Things under Control, Otherwise …” - Schadde, Anne (Homœopathic Links, 2015)
Homeopathic provings give us good knowledge about the symptoms of a substance. But we can better learn from cases in which the remedy acted in a helpful way. Nevertheless, provings are of great importance because it is difficult to know about an energetic field of the substance without a well-done proving. Heidi Brand and Norbert Groeger conducted the proving of the algae Chara intermedia. Hahnemann states in Organon §141: “…the most excellent provings remain those that the healthy, unprejudiced, conscientious and fine-feeling physician employs upon himself…” I was part of the trituration process of the algae Chara intermedia and I could observe the proving. So I got an impression about the rigidity, being stuck in a situation without way out, confirmed later in the proving. This new proving together with good cases after years of experience with the remedy is now published in English.
Keywords: Multiple sclerosis; Control; Rigidity; Loneliness; Algae; Water plant; Chara intermedia